Sistemas de gestión de piso de planta. Ideas para implementación en una companía - Moro, Gastón J. L. (2019)
In the same way that it is necessary to study the context before setting objectives ambitious and conscientiously propose achievable objectives, implement a Floor floor management tool must have the same principle. Prior to begin the design of dashboards and control, must be evaluated, on the one hand, the availability of current resources, in order to know what management perimeter is possible cover and, on the other hand, measure the reliability of the indicators used, with the purpose of making decisions on solid foundations. When a company decides to carry out a methodology for the implementation of control panels, the direction in charge of allocating the necessary resources, does not take the enough time to know if the people assigned to the methodology really have the time required to participate and achieve the expected results. Moreover, if the The company in question has several years in the market and underwent continuous changes of management, management does not know the detail of the tasks of each lower command as also if these are and will continue to be required for the new management. This Master's Thesis is dedicated to the Management of companies; in consecuense, initially it will focus on middle managers to demonstrate through their development, how it contributes to improve all levels of management. For this purpose, a Management System will be designed for the floor of the plant oriented to reach the production objectives and consequently, the economic results of the Company. In turn, the regulation model considered will allow a more management change effective and resistant to changes in the direction of the Company, generating greater participation in all levels of operation. Considering as a model a company in the field of plastics with more than 40 years of presence in the market, which has started its activities as a Family Company and today continues as a multinational, this Master thesis work will demonstrate the advantages of apply the methodology described in comparison to other tools aimed at same end. Finally, this thesis will constitute a guide for the effective implementation of tools of plant floor management.